Evaluation of microcomputer utilization in small- and medium-sized businesses - J. J.D. Havenga; P. J.S. Bruwer (South African Journal of Business Management, 1990)
This paper presents the result of an empirical study on the use of microcomputers by small and medium-sized businesses in South Africa. A number of countries were included in the survey. The purpose of this study was to establish, through the use of 51 variables in the project, what major problems small and medium-sized businesses experience in the use of microcomputers in a developing region such as southern Africa. Special emphasis was placed on the main reasons for purchasing microcomputers, types of software used, as well as training and experience in handling this equipment in the management of a small business. Major findings included a greater computer literacy amongst users, with a strong tendency towards computer application for more sophisticated purposes such as decision making means of support.
Keywords: 650